The Implementation of Occupational Health and Safety - Nasution, Muhammad Islam; Mufidah, Ida Umarul; Pongmasangka, Nico Linggi; Ahmad, Eka Fitriani; Rojak, Octovianus Bin; Aryadi, Valyaty Frisa (Media Karya Kesehatan, 2023)
Batik is a traditional process of repeatedly applying wax and dye on fabric to produce intricate and colourful patterns. Occupational safety and health issues arise among workers due to improper positioning during the mencanting process or exposure to risk factors in the workplace. This community service aims to implement workplace climate measurement using the Wet Bulb Globe Temperature (WBGT) index, work fatigue using a reaction timer test, light intensity with a lux meter in the mencanting area, musculoskeletal pain using the Nordic Body Map (NBM) questionnaire, as well as promoting occupational safety and health materials to 8 participants whom are workers at Small and Medium-sized Enterprise (UKM) Sanggar Batik Cirebon. The measurement results showed the average (WBGT) workplace climate index was 28.13 °C; the average work fatigue was 531.48 milliseconds; the average range of light intensity was 45.20 Lux - 85.33 Lux; and the average NBM score was 47.13. During the delivery of the occupational safety and health promotion materials, the participants appeared enthusiastic and motivated.  Keywords:  Ergonomic, light intensity, musculoskeletal, work fatigue.